(3QSGdI aj Yed GdejRGf GdWHjYi GdPi jYde Hg cejI eG aj GdLSe GdeQcH ef eYOfjf eNJdajf aj cd hGMO efgG ef ZjQ gOe GdTcd GdeQcH Ydjgs - (3eMeO Jbj GdOjf Hf GdbGVj eYQha GdMfaj GdOeTbjs
(3ChdgG (B:s
(3hHYO agPg QSGdI dWjaI ai Yed GdejRGf GdWHjYi GdPi jYde Hg cjajI eG ai GdLSe GdeQcH ef eYOfjjf s
(3BNQgG (B:s
(3hai gPG GdbOQ caGjI hHGddg GdJhajb hGdgOGjI Edi ShGA GdWQjb s
(3ai BNQgG LOhd UZjQ HjGf GdCLSGe hChRGfgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B1035 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B56 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs